Corporate taxation: High profits, moderate tax revenue - Stefan Bach (DIW Economic Bulletin, 2013)
If the revenue from corporate taxation in Germany is divided by the corporate income figures from national accounts, companies' average tax burden for the period 2001 to 2008 is 21 percent. This rate is considerably lower than the statutory tax rates for this period. The reason for this is that tax-reported corporate income was well below macroeconomic corporate income. This taxation gap was something in the order of at least 120 billion euros in 2007, or almost five percent of gross domestic product (GDP). Moreover, the high level of tax losses and tax losses carried forward is significant. The losses carried forward for corporate income tax rose to 568 billion euros by the end of 2007. This was equivalent to 23.5 percent of GDP and 3.5 times the corporate income tax base for that year. As a result of broadening the tax base as part of the corporate tax reform of 2008, the taxation gap has diminished significantly, but it was still at about 90 billion euros, or 3.7 percent of GDP. Due to a lack of detailed statistics, it is currently not possible to accurately identify the reasons for the difference between macroeconomic profit figures and the corporate tax base.
Keywords: H25; H26; H22; 330; corporate income tax; implicit tax rates; tax base erosion